HPTLC method for quantitative determination of hydroxycinnamic acid derivatives in Solanum lycopersicum (Bangladesh Journal of Pharmacology, 2018)
The study was aimed to validate and optimize high performance thin layer chromatography (HPTLC) method for the determination of phenolic compound hydroxycinnamic acid derivatives from the fruits of Solanum lycopersicum (tomato). The presence of caffeic acid and coumaric acid in the aqueous extracts of S. lycopersicum was observed in spectrophotometer at 200-400 nm. The phenolic functional group was recorded by FTIR analysis. In the HPTLC analysis, the pre-coated silica gel was used as the stationary phase. The solvent mixture containing toluene:ethyl acetate:formic acid:methanol (3:6:1.6:0.4) was identified as an optimum ratio were used as a mobile phase. The chromatograms of the extract was scanned by densitometer at 327 nm.  The Rf values (0.67 and 0.69) and finger print data were recorded by WIN CATS software. The developed HPTLC methods for bioactive marker compounds present in the fruit were found to be simple, accurate, and economical.